Endovascular management of carotid-cavernous fistulas: a 16-year retrospective analysis of multimodal treatment strategies and long-term clinical outcomes - Nurimanov, Chingiz; Mammadinova, Iroda; Menlibayeva, Karashash; Kydyrmoldin, Yeldar; Duisengali, Ramazan; Kerimbayeva, Diana; Akshulakov, Serik; Makhambetov, Yerbol (Frontiers in Neurology, 2025)
BackgroundCarotid-cavernous fistulas (CCFs) are abnormal connections between the carotid artery and/or its branches and the cavernous sinus, potentially resulting in significant complications, including visual impairment and neurological deficits. Timely diagnosis and appropriate therapeutic intervention are critical to minimizing the risk of adverse outcomes. Over the years, endovascular techniques have become the preferred method for treating CCFs, offering high success rates with fewer complications. This study aims to study the clinical and radiological outcomes of patients with CCFs treated with endovascular approaches, and to identify key prognostic factors associated with treatment efficacy and symptomatic resolution.MethodsA retrospective analysis was conducted of patients diagnosed with carotid-cavernous fistulas (CCFs) and treated at the National Center for Neurosurgery in Astana, Kazakhstan, between 2008 and 2024. A total of 71 patients underwent endovascular embolization using either transarterial or transvenous techniques. According to the Barrow classification, type A CCF were observed in 62 patients (87.3%), type D in 7 patients (9.9%), and types B and C in 1 patient each (1.4%). Collected data included patient demographics, type of embolic materials utilized, number of procedures performed, treatment approach, and corresponding radiological and clinical outcomes.ResultsAmong the 71 patients included in the study, 80.3% achieved complete clinical resolution, 15.5% demonstrated partial improvement, and 4.2% experienced no clinical benefit. The mean age was 35.7 ± 12.9 years, with 71.8% males. Clinical outcomes were significantly associated with complete occlusion following the initial intervention (p < 0.001), with 96% of these patients achieving full symptom resolution. Imaging follow-up was available in all patients, with complete occlusion confirmed in 65 cases (91.5%) on MRI at 6 months. Other variables, including distal internal carotid artery flow (p = 0.145), number of interventions (p = 0.838), treatment approach (p = 0.529), and type of embolic agent employed (p = 0.778), did not demonstrate a statistically significant association with clinical outcomes.ConclusionEndovascular embolization is a safe and effective first-line treatment modality for CCFs. Both transarterial and transvenous approaches offer comparable rates of clinical success. Achieving complete occlusion is a critical determinant of favorable clinical outcomes and is associated with a reduced risk of treatment-related complications.